United : captured by God's vision for diversity - Newbell, Trillia J. (Chicago : Moody Publishers, 2014)
"It's time to capture a glimpse of God's magnificent creativity. In the pages of United, Trillia Newbell reveals the deeply moving, transforming power of knowing--really knowing--someone who is equal yet unique. As we learn to identify in Christ rather than in our commonalities, we begin to experience the depth and power of gospel unity."--Page [4] of Cover.
My new identity -- My white church -- Longing for diversity -- God's provision of diversity -- Different but the same -- Growing together in Christ -- His bride -- A difficult pursuit -- For our kids.
Includes bibliographical references.
Keywords: Church and minorities; Race relations -- Religious aspects -- Christianity; Ethnic relations -- Religious aspects -- Christianity; Reconciliation -- Religious aspects -- Christianity; Church and minorities; Ethnic relations -- Religious aspects -- Christianity; Race relations -- Religious aspects -- Christianity; Reconciliation -- Religious aspects -- Christianity